An experimental study of some two-dimensional antiferromagnets - Clarke, S; Clarke, Simon (1994)
﻿ This thesis discusses the investigation of the two-dimensional S = œ Heisenberg antiferromagnet copper formate tetrahydrate (CFTH) and the layered triangular lattice material NaTi02 which was thought to be a candidate for the possession of a non-classical antiferromagnetic ground state due to the frustration inherent in a triangular antiferromagnet. Single crystals of CFTH are investigated using elastic, quasielastic and inelastic neutron scattering, electron spin resonance (ESR) spectroscopy and DC magnetometry. Using the appropriate theory, these measurements are used to determine values for the terms in the Hamiltonian which describes the interactions between the Cu2+ ions in this material. The Hamiltonian is compared with that of La2Cu04, and the two are determined to be quite similar. There does not appear to be any evidence for a non-classical ground state in either material. This was proposed to exist in La2Cu04 to account for the superconductivity of doped samples. The difficulties in preparing pure NaTi02 have been surmounted, and a technique is described for preparing powder samples with very reproducible structural and magnetic properties. The structural properties have been investigated using X-ray and neutron diffraction, the latter at temperatures between 100 K and room temperature. The magnetic properties have been probed using DC magnetometry and ESR spectroscopy. The sample dependence of the structural and magnetic properties of samples prepared in slightly different ways is discussed. The temperature dependence of the magnetic susceptibility and of the structural parameters is explained by comparison with other oxides and chlorides of trivalent Ti and V, many of which show similar behaviour. The magnetic and structural changes which occur between 200 and 250 K are assigned to changes in the Ti-Ti bonding within the layers, which leads to a transition between two metallic states with subtle differences in their band structures.